CUSTOMER AWARENESS TOWARDS HEALTH INSURANCE WITH SPECIAL REFERENCE TO BHUBANESWAR CITY - Tripathy, Dr. P.; Kanungo, Mr. S.S.; Roy, Mr. Satyajit (IJRDO - Journal of Business Management, 2018)
Growing demand for modern medical care, brought on by a rapidly, expanding population, rising literacy levels, and technological advancement lead to high expectation from the health services. This has shifted demand in favour of health care. Good Health confers on a person or groups’ freedom from illness - and the ability to realize one’s potential. Health is therefore best understood as the indispensable basis for defining a person’s sense of well being. Health insurance is an insurance against the risk of incurring medical expenses among individuals. Health insurance remains vastly under-developed in India. An analysis of financing of hospitalization shows that large proportion of people borrows money or sells assets to pay for hospitalization. Majority of Indians are more vulnerable to major ailments. Marketing of health insurance policies become paramount important to help people to meet out the untoward expenses arising out of unexpected ailments. It will be a win-win situation for public and companies of increasing the penetration of health insurance products to its fullest potential. The benefit of health insurance has to be extended to the excluded population too. Clearly there is an urgent need to expand the health insurance net in India. In such a situation it is essential to understand the consumers how far they are interested in buying health insurance, consumers perception is to be recorded, it is essential to limit the out-of-pocket expenses of the consumers, and suggest and bring an awareness to the consumers how health insurance would help in reducing their financial burden during hospitalization. The percentage of India’s national budget allocated to the health sector remains one of the lowest in the world, and healthcare expenditures are largely out-of-pocket (OOP). Currently, efforts are being made to expand health insurance coverage as one means of addressing health disparity and reducing catastrophic health costs. Identification of six key topics demand more in-depth research, among others: (1) public awareness and understanding of insurance; (2) misunderstanding of insurance and how this influences health care utilization; (3) differences in behavior patterns in cash and cashless insurance systems; (4) impact of insurance on quality of care and doctor-patient relations; (5) (mis)trust in health insurance schemes; and (6) health insurance coverage of chronic illnesses, rehabilitation and OOP expenses. This paper identifies the determinants of awareness of health insurance in Odisha. The present study was carried out in Bhubaneswar city of Odisha. Since the main objective of the study was to analyze determinants of awareness of the health insurance, we concentrated on the variables like the Age, Education, Gender, Occupation, Income, type of the family, and Health expenditure etc. Using pretested structured questionnaire, the primary data have been collected purposively, by covering the wide range of demographic, economic and social factors, from the randomly chosen two hundred respondents from the study area. Simple statistical tools such as descriptive statistics and along with factor analysis to identify the factors determining the awareness of the health insurance.